Development of a hybrid mixed-mode solar dryer for product drying. Issue 3 (March 2023) - Afzal, Arslan; Iqbal, Tahir; Ikram, Kamran; Anjum, Muhammad Naveed; Umair, Muhammad; Azam, Muhammad; Akram, Sajeela; Hussain, Fiaz; Ameen ul Zaman, Muhammad; Ali, Abid; Majeed, Faizan
Abstract: Sun drying in the open air is quite popular worldwide. However, the use of solar dryers to preserve various perishable agricultural products is a relatively new area of study, and the long-term effects of this method are not yet fully understood. The slow drying process in direct sunlight can contaminate the dried materials by soil and insects. To overcome these challenges, we devised a sun drying system that included a heating part, a drying area, a portable stand, fans, and a 50-W photovoltaic panel. An alternate energy source was used to power the drying process during cloudy days and at night. Fresh Freestone peach, Golden apple, and Anaheim chilies weighing 10 kg each with the initial moisture content of 89%, 87%, and 75% on a wet basis (w.b), respectively, were used in the experiments. The final moisture content of the samples was reduced by an average of 16%, 15%, and 11% for Freestone peaches, Golden apples, and Anaheim chilies, respectively. The quality analysis was carried out to determine sample composition, total bacteria, and color of dried products. The results indicated that the dried products met the recommended quality standards for food products in terms of composition, total bacteria, and color. This research supports the use of a hybrid mixed-mode solar dryer for drying a wide range of perishable agricultural products.